1998
DOI: 10.1094/phyto.1998.88.6.530
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Effects on Sugarcane Growth, Pythium Root Rot, and Pythium arrhenomanes

Abstract: Six herbicides were evaluated for their effects on Pythium root rot and growth of sugarcane in greenhouse experiments and on in vitro mycelial growth rate of Pythium arrhenomanes. Pendimethalin and atrazine were most inhibitory to mycelial growth, but neither reduced root rot severity. Asulam, atrazine, and metribuzin were not phytotoxic to sugarcane and did not affect root rot symptom severity in clay loam or silt loam field soils. Atrazine and metribuzin increased shoot number, and atrazine increased total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…From literature, high silt content favours plant diseases caused by Pythium spp. Sugarcane root rot caused by Pythium arrehenomanes was severe in silt loam soil (Dissanayake et al, 1998). Johnson et al (1978) reported abundant Pythium ultimum in cotton seedlings growing in silt loam soils.…”
Section: Article In Pressmentioning
confidence: 98%
“…From literature, high silt content favours plant diseases caused by Pythium spp. Sugarcane root rot caused by Pythium arrehenomanes was severe in silt loam soil (Dissanayake et al, 1998). Johnson et al (1978) reported abundant Pythium ultimum in cotton seedlings growing in silt loam soils.…”
Section: Article In Pressmentioning
confidence: 98%
“…Besides affecting target weeds, herbicides may interact in several ways with plants and soil microorganisms that may influence the plant-pathogen relationship (Altman and Rovira 1989;Dissanayake et al 1998). It is known that herbicides produce changes in the physiology and development of crop plants, thus increasing disease susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, root rot symptom severity was not reduced. However, atrazine inhibited mycelial growth of P. arrenomanes in vitro when applied at the label rate (Dissanayake et al, 1998). The mechanism of root and shoot growth stimulation of triazine herbicides was shown to be an increase in the activity of nitrite reductase and transaminase (Ries et al, 1967) and seem also to refer to pea and sweet corn (Wu et al, 1972).…”
Section: Triazine Herbicidesmentioning
confidence: 97%
“…Thus, the herbicide seems to reduce the plant's ability to protect itself against pathogens. Glyphosate was also shown to be phytotoxic to sugarcane and herbicide treatment resulted in increased disease severity caused by Pythium arrenomanes (Dissanayake et al 1998). Furthermore, glyphosate application caused injury and death of Lolium multiflorum as a result of increased Pythium root rot (Kawate and Appleby, 1987).…”
Section: Soil Pathogensmentioning
confidence: 99%
See 1 more Smart Citation